(untitled) (Research, Society and Development, 2022)
Obstetric violence is defined as a set of actions that harm women’s health during any period in the pregnancy cycle, whether in prenatal care, childbirth or puerperium The current study aims to identify the role of nursing in relation to the prevention of obstetric violence . This is an integrative literature review, carried out in June and July 2022 through electronic searches in the LILACS, SCIELO and BDENF databases. The search strategies allowed us to identify 325 articles, applying the inclusion criteria, 316 were excluded, in total 9 articles were selected because they met all the requirements. The results show that the role of nursing in the prevention of obstetric violence has an extremely important role, because it is the category of professionals who are closest to the parturient, so some of the main measures taken to ensure that this prevention occurs help can be mentioned whenever necessary, stable education and humanization of assistance. Therefore, it is concluded that nurses must guarantee the assistance of women in a dignified and respectful way, so that pregnancy and childbirth are not traumatic moments due to the violation of rights.